The ghost of freedom a history of the Caucasus - King, Charles, 1967- (Oxford University Press, 2008)
The Caucasus mountains rise at the intersection of Europe Russia and the Middle East. Home to a dizzying array of ancient cultures, the Caucasus has often been the object of imperial ambition. This book reveals how tsars, revolutionaries and adventurers have contributed to the fascinating history of this borderland.